1982
DOI: 10.1007/bf00200171
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of the leukocytes of melanoma patients and control donors, including pregnant women, with melanoma- and fetus-derived materials

Abstract: Using a one-stage capillary leukocyte migration inhibition assay, we examined peripheral blood leukocytes from 97 patients with malignant melanoma, 194 pregnant women, and 123 non-pregnant donors for their reactivity with materials from fetal and melanomatous tissues. As in previous studies, we found melanoma extracts selectively to inhibit melanoma patients' leukocytes. First-trimester fetal extracts also selectively inhibited melanoma patients' leukocytes, suggesting their cross-reactivity with melanoma-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A review of previous results from in vitro studies of cellular and humoral immunity suggests that human cancers and fetal tissues share immunogenic antigens [10,19,21,28,39,43,70]. However, the results provide a wide discrepancy in the time of fetal expression of the antigens, the specificity of the antigens, and the effect of fetal antigens on sensitization of pregnant women.…”
Section: Discussionmentioning
confidence: 87%
“…A review of previous results from in vitro studies of cellular and humoral immunity suggests that human cancers and fetal tissues share immunogenic antigens [10,19,21,28,39,43,70]. However, the results provide a wide discrepancy in the time of fetal expression of the antigens, the specificity of the antigens, and the effect of fetal antigens on sensitization of pregnant women.…”
Section: Discussionmentioning
confidence: 87%
“…Melanomas are relatively often diagnosed during pregnancies; it has led to the speculation that certain hormone effects and immunosuppression in pregnancy may induce malignant transformation (Sadoff et al, 1973;Cochran et al, 1982). However, none of the studies showed that the risk for melanoma occurring is higher during pregnancy.…”
Section: The Impact Of Pregnancymentioning
confidence: 99%